Transforming growth factor β-mediated site-specific Smad linker region phosphorylation in vascular endothelial cells - Kamato, Danielle; Rostam, Muhamad Ashraf; Piva, Terence J.; Rezaei, Hossein B.; Getachew, Robel; Thach, Lyna; Bernard, Rebekah; Zheng, Wenhua; Little, Peter J.; Osman, Narin (Wiley, 2014)
Objectives Transforming growth factor (TGF)-β regulates the function of vascular endothelial cells and may be involved in endothelial dysfunction. The canonical TGF-β pathway involves TGF-β receptor-mediated carboxy-terminal phosphorylation of Smad2; however, TGF-β signalling also activates numerous serine/threonine kinases that phosphorylate Smad2 in its linker region. The expression of phosphorylated Smad linker proteins were determined following TGF-β stimulation in the absence and presence of different serine/threonine kinase inhibitors in vascular endothelial cells. Methods Proteins were quantified by Western blotting using specific antibodies to individual phosphorylated Smad2 linker region residues. Key findings TGF-β mediated the phosphorylation of all four Smad2 linker region residues of interest. Erk and Jnk specifically phosphorylate Ser245 while all mitogen-activated protein kinases phosphorylate Ser250 and Ser255. Thr220 and Ser245 are phosphorylated by phosphoinositide 3 kinase (PI3K), while Ser255 was phosphorylated by the PI3K/Akt pathway. CDK and GSK-3 were shown to phosphorylate Thr220 and Ser245. TGF-β also mediated plasminogen activator inhibitor-1 gene expression that was attenuated by p38 and CDK inhibitors. Conclusions TGF-β-mediated phosphorylation of individual serine/threonine sites in the linker region of Smad2 occurs in a highly specific manner by kinases. These phosphorylations provide an opportunity to further understand a therapeutically targeted and very specific signalling pathway in vascular endothelial cells.